2016
DOI: 10.1037/tra0000049
|View full text |Cite
|
Sign up to set email alerts
|

Coverage of child maltreatment in abnormal psychology textbooks: Reviewing the adequacy of the content.

Abstract: Abnormal psychology courses introduce undergraduate students to the range, causes, and treatments of psychological disorders. These courses present important opportunities to instruct students about disorders and treatments associated with childhood maltreatment (CM) as well as its prevalence. Little research has examined the adequacy with which abnormal psychology textbooks present information about CM. The present study reviewed the CM content of 10 abnormal psychology textbooks. The content was assessed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 77 publications
2
27
0
Order By: Relevance
“…Subsequent studies have also found that individuals with DID are no more suggestible or prone to creating false memories than are individuals with posttraumatic stress disorder (PTSD), actors simulating DID, or healthy controls (Vissia et al., 2016). Despite the lack of support for this theory, it continues to be presented in many psychology textbooks as if it is a scientifically based explanation for dissociation (Wilgus, Packer, Lile-King, Miller-Perrin, & Brand, 2015). This misinformation has contributed to skepticism among many people about the validity of dissociation and the DDs, despite the substantial research showing both are common, neurologically linked psychological problems caused by trauma and disruptions in attachment.…”
Section: The Trauma Versus Fantasy/sociocultural Model Of Dissociationmentioning
confidence: 99%
“…Subsequent studies have also found that individuals with DID are no more suggestible or prone to creating false memories than are individuals with posttraumatic stress disorder (PTSD), actors simulating DID, or healthy controls (Vissia et al., 2016). Despite the lack of support for this theory, it continues to be presented in many psychology textbooks as if it is a scientifically based explanation for dissociation (Wilgus, Packer, Lile-King, Miller-Perrin, & Brand, 2015). This misinformation has contributed to skepticism among many people about the validity of dissociation and the DDs, despite the substantial research showing both are common, neurologically linked psychological problems caused by trauma and disruptions in attachment.…”
Section: The Trauma Versus Fantasy/sociocultural Model Of Dissociationmentioning
confidence: 99%
“…Studies of individuals with PTSD, both with and without borderline personality disorder, have found that higher dissociation levels predict poor response to standard treatments, such as eye movement desensitization and reprocessing (EMDR) and dialectical behavior therapy (DBT; Bae, Kim, & Park, ; Kleindienst et al., ). Despite these data, most psychiatric and psychology textbooks fail to present empirical research about DDs, or they provide inaccurate or sensationalized information about diagnosis and treatment of DDs (Loewenstein et al., ; Wilgus, Packer, Lile‐King, Miller‐Perrin, & Brand, ).…”
mentioning
confidence: 99%
“…Despite the prevalence and negative outcomes for survivors of CM and child trauma, as well as their increased need for treatment (Bartlett et al, 2018; Hanson & Lang, 2016), undergraduate psychology textbooks provide inadequate coverage of CM, including limited discussion of the risk factors, myriad consequences, and treatments related to CM (Brand & McEwen, 2014; Kissee, Isaacson, & Miller-Perrin, 2014; Wilgus, Packer, Lile-King, Miller-Perrin, & Brand, 2016). These textbook deficiencies may reflect that few people in the mental health field, including textbook authors, have received training about trauma; therefore, few mental health professionals recognize its prevalence and impact (Brand, 2016; Courtois & Gold, 2009).…”
mentioning
confidence: 99%